Pengaruh Disiplin Kerja terhadap Kinerja Karyawan PT. Sari Burger King Cabang Pekanbaru - Ikhsan, Wandi Nur; A, Afrizal; M, Mukson (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted at PT. Sari Burger King Pekanbaru Branch, the respondents of this study were 75 people, where the sample of this study were employees of PT. Sari Burger King Pekanbaru Branch. The purpose of this study was to determine the Effect of Work Discipline on Employee Performance at PT. Sari Burger King Pekanbaru Branch with the results of the hypothesis test showing that t count (6.415) t table (1.9929) with sig 0.000 sig 0.05, so it can be concluded that there is a significant influence on if Work Discipline on Employee Performance at PT. Sari Burger King Pekanbaru Branch. Based on the calculation table, the correlation value (R) produced is 0.600. So it can be concluded that there is a high relationship between the independent variables and the dependent variable. While the R Square value is 0.361. This shows that the Work Discipline variable as a whole has an influence of 36.6% on Employee Performance while the remaining 63.3% is influenced by other variables not examined in this study, for example: leadership style, compensation, etc.